Review Of Removal of Heavy Metal Ions from Water by Complexation-Assisted Ultrafiltration - Azeez Sakran Abed (Academia Open, 2026)
The escalating contamination of water resources by heavy metal ions poses critical environmental and public health challenges, necessitating efficient remediation technologies. This review examines the application of Complexation-Assisted Ultrafiltration (CP-UF), alternatively termed Polymer-Enhanced Ultrafiltration (PEUF), as an advanced membrane-based separation process for removing toxic heavy metals from aqueous solutions. The study systematically analyzes two distinct approaches: synthetic polymers including Polyethylene Glycol (PEG 5000) and Diethylaminoethyl-cellulose (DEAE-cellulose) for zinc and cadmium removal, and natural biopolymer Carboxymethyl Cellulose (CMC) for copper, nickel, and chromium elimination. Through comprehensive evaluation of experimental data from ultrafiltration membrane systems operated under varying conditions, the research demonstrates that DEAE-cellulose achieves exceptional rejection rates up to 99% for Zn(II) at pH 9.0 and 300 kPa pressure, while CMC exhibits superior performance exceeding 97% rejection for Cu(II), Ni(II), and Cr(III) at neutral to alkaline pH conditions. Critical operational parameters including solution pH, applied transmembrane pressure, membrane molecular weight cut-off, and polymer concentration significantly influence both permeate flux and metal ion retention efficiency. The novelty of this work lies in the comparative assessment of synthetic versus natural polymeric ligands, revealing that amino-functionalized DEAE-cellulose forms stable coordination complexes through nitrogen electron donation, whereas CMC utilizes carboxyl and hydroxyl groups for metal binding in pH-dependent octahedral or square planar configurations. Furthermore, the study establishes the economic and environmental feasibility of polymer regeneration through pH adjustment or chemical cleaning cycles, enabling multiple reuse iterations. These findings advance membrane separation theory by validating osmotic pressure models in complexation-ultrafiltration systems and provide practical implications for industrial wastewater treatment, particularly for low-concentration heavy metal effluents where conventional precipitation methods prove inadequate, thereby supporting sustainable water resource management and regulatory compliance in chemical engineering applications.Keywords : Filtration, Complexation-Ultrafiltration, Polymer-Enhanced Ultrafiltration (PEUF), Heavy Metal Removal, Water-Soluble PolymersHighlight : DEAE-cellulose mencapai rejeksi 99% untuk Zn(II) pada pH 9,0 dengan tekanan 300 kPa CMC menghasilkan rejeksi >97% untuk Cu(II), Ni(II), dan Cr(III) pada pH ≥7 Regenerasi polimer melalui penyesuaian pH memungkinkan penggunaan berulang dalam siklus pemisahan logam.